Better humans, better performance : driving leadership, teamwork, and culture with intentionality - Rea, Peter J.; Stoller, James K.; Kolp, Alan, 1944- (McGraw Hill, 2023)
"Virtue is more than a word; it is a way to live. When applied to our professional life, when we cultivate virtue in ourselves and others and also flourish as a human. When applied to organizational life organizational engagement goes up. When we cultivate virtue, we deepen and strengthen relationships at work and in life"--